Perception of visual apparent motion is modulated by a gap within concurrent auditory glides, even when it is illusory - Wang, Qingcui; Guo, Lu; Bao, Ming; Chen, Lihan (Frontiers in Psychology, 2015)
Auditory and visual events often happen concurrently, and how they group together can have a strong effect on what is perceived. We investigated whether/how intra- or cross-modal temporal grouping influenced the perceptual decision of otherwise ambiguous visual apparent motion. To achieve this, we juxtaposed auditory gap transfer illusion with visual Ternus display. The Ternus display involves a multi-element stimulus that can induce either of two different percepts of apparent motion: ‘element motion’ or ‘group motion’. In “element motion”, the endmost disk is seen as moving back and forth while the middle disk at the central position remains stationary; while in “group motion”, both disks appear to move laterally as a whole. The gap transfer illusion refers to the illusory subjective transfer of a short gap (around 100 ms) from the long glide to the short continuous glide when the two glides intercede at the temporal middle point. In our experiments, observers were required to make a perceptual discrimination of Ternus motion in the presence of concurrent auditory glides (with or without a gap inside). Results showed that a gap within a short glide imposed a remarkable effect on separating visual events, and led to a dominant perception of group motion as well. The auditory configuration with gap transfer illusion triggered the same auditory capture effect. Further investigations showed that visual interval which coincided with the gap interval (50-230 ms) in the long glide was perceived to be shorter than that within both the short glide and the ‘gap-transfer’ auditory configurations in the same physical intervals (gaps). The results indicated that auditory temporal perceptual grouping takes priority over the cross-modal interaction in determining the final readout of the visual perception, and the mechanism of selective attention on auditory events also plays a role.